Effects of binary dance rhythm compared with quaternary dance rhythm in fatigue, sleep, and daily sleepiness of individuals with Parkinson's disease: A randomized clinical trial - Moratelli J.A.* (2022)
© 2022 Universidade Estadual Paulista - UNESP. All rights reserved.Aim: People with Parkinson's disease constantly demonstrate low levels of physical activity, which is why dance has become increasingly important for the treatment of the disease. This study aimed to analyze the influence of binary and quaternary rhythm on fatigue, sleep, and daytime sleepiness in individuals with Parkinson's disease. Methods: 31 individuals participated in this randomized clinical trial with a mean age of 66.6 ± 10.2 years, 71% were male and 29% were female, allocated into two groups, binary and quaternary, where they participated in different dance interventions lasting 12 weeks. A questionnaire was applied including personal and clinical information; Mental State Mini-Examination (MMSE), Hoehn and Yahr (H&Y), Fatigue Severity Scale (FSS), Sleep Scale for Parkinson's Disease (PDSS), and Daytime Sleepiness Epworth Scale (ESS). Results: The groups that participated in binary rhythm classes showed improvement in sleep quality and daytime sleepiness after 12 weeks of intervention. However, no significant differences were found in the group that participated in the quaternary rhythm classes. Moreover, it was noted that the binary group managed to raise the heart rate during the 12 weeks of intervention, given that these results were not obtained in the quaternary group. Conclusion: The results showed the effectiveness of binary rhythm on nonmotor symptoms and heart rate increase in individuals with Parkinson's disease. Thus, it is concluded that the binary rhythm was more effective than the quaternary rhythm.